BOOK REVIEW: ENGINEERING PSYCHOLOGY AND HUMAN PERFORMANCE - Widura Imam Mustopo (Fakultas Seni Rupa dan Desain ITB, 2021)
This book was written to address the gap between problems of system design and the results of theoretical research in the study of cognitive psychology, experimental psychology, and human performance. Many of the built human-machine systems do not work optimally due to forced demands or requirements on humans as users, which is not in accordancewith the way humans observe, pay attention, understand, think, remember, and decide, as well as act, or in other terms the way people perform or process information. Over the past six decades, tremendous efforts have been made to understand and model human information processing and human performance. Another purpose of this book is to show how theoretical developments have taken place and been applied to improve productivity and safety of humanmachine interactions.